How to Manage Yard Wastes to Protect Surface Water Resources - Mary G. Lusk (EDIS)
Several of the Florida-Friendly LandscapingTM (FFL) principles provide guidance on how to reduce the amount of nutrients applied to and mobilized from urban landscapes to water resources. Principle # 7: Recycle Yard Waste and Principle # 9: Protect the Waterfront are two examples from this program that can be important steps towards protecting Florida’s water. The purpose of this publication is to provide guidance on specific actions that you can take to help reduce nutrient inputs to our water, with a focus on the FFL Principles  # 7 and # 9. This publication is intended primarily for urban residents who manage their own landscapes and may also be used by landscaping professionals, homeowner’s associations, and municipal decision makers.